2007
DOI: 10.3177/jnsv.53.419
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Effects of .GAMMA.-Glutamyl Carboxylase Gene Polymorphism on the Correlation between the Vitamin K Status and .GAMMA.-Carboxylation of Osteocalcin in Young Males

Abstract: Summary Vitamin K is a cofactor for ␥ -glutamyl carboxylase (GGCX), which is an essential enzyme for the ␥ -carboxylation of vitamin K-dependent proteins such as osteocalcin (OC). Associations among dietary vitamin K intake, vitamin K status, and bone metabolism have not been thoroughly investigated. Recently, it has been reported that single nucleotide polymorphisms of GGCX (R325Q, 974G Ͼ A) were associated with age-related bone loss and the kinetic affinity for the substrate. In the present study, we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
2
9
2
Order By: Relevance
“…Previous studies suggested %ucOC as a marker of vitamin K intake, but we could not confirm these findings. The correlation between %ucOC and vitamin K intake in our study was much lower than in previous studies, which showed correlations of -0.21 and -0.33 respectively [ 25 , 26 ]. However, in these studies vitamin K intake was measured with 3 day food- records before the day of blood examination [ 25 , 26 ].…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Previous studies suggested %ucOC as a marker of vitamin K intake, but we could not confirm these findings. The correlation between %ucOC and vitamin K intake in our study was much lower than in previous studies, which showed correlations of -0.21 and -0.33 respectively [ 25 , 26 ]. However, in these studies vitamin K intake was measured with 3 day food- records before the day of blood examination [ 25 , 26 ].…”
Section: Discussioncontrasting
confidence: 95%
“…The correlation between %ucOC and vitamin K intake in our study was much lower than in previous studies, which showed correlations of -0.21 and -0.33 respectively [ 25 , 26 ]. However, in these studies vitamin K intake was measured with 3 day food- records before the day of blood examination [ 25 , 26 ]. The validity of the FFQ may explain the difference between our study and previous studies.…”
Section: Discussioncontrasting
confidence: 95%
“…In humans, γ-carboxylation is controlled by the vitamin K dependent enzyme γ-glutamyl carboxylase (GGCX). Functional polymorphisms of GGCX and the vitamin K epoxide reductase (VKORC1) gene were associated with uncarboyxlated OCN levels [17,24]. Transcriptional regulation of BGLAP in humans is controlled by promoter binding of a complex that includes the transcription factor RUNX2, coactivator CBP/p300, and corepressor HDAC3 at the promoter [15,21].…”
Section: Discussionmentioning
confidence: 99%
“…The fraction of OC that has undergone imperfect gamma-carboxylation is referred to as undercarboxylated OC (ucOC), and cannot be shifted from blood vessels to bone due to a decrease in the affinity for Ca 2+ and hydroxyapatite (Hauschka et al 1989). Since vitamin K is involved in this carboxylation, inadequate levels of vitamin K lead to increased serum ucOC levels (Sokoll and Sadowski 1996;Binkley et al 2002;Sogabe et al 2007). Serum ucOC levels are thus regarded as a marker of vitamin K deficiency.…”
mentioning
confidence: 99%